Progress in VLSI design and test : 16th International symposium, VDAT 2012, Shibpur, India, July 1-4, 2012. Proceedings - Chattopadhyay, Sanatan; Chattopadhyay, Santanu; Rahaman, Hafizur (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 16th International Symposium on VSLI Design and Test, VDAT 2012, held in Shibpur, India, in July 2012. The 30 revised regular papers presented together with 10 short papers and 13 poster sessions were carefully selected from 135 submissions. The papers are organized in topical sections on VLSI design, design and modeling of digital circuits and systems, testing and verification, design for testability, testing memories and regular logic arrays, embedded systems: hardware/software co-design and verification, emerging technology: nanoscale computing and nanotechnology.